A Religious Tolerance and Harmony the Qur'anic Perspective - Yusuf, Choirul Fuad (Center for Research and Development of Religious Literature and Heritage, 2012)
The religious tolerance and harmony is something necessary to develop due to the need of global security and peace today. For this purpose, all religions have to be fairly “tolerant” to others. Islam as a revealed religion, whatever its motive, is often perceived and accused as the religion of intolerance and violence. Some political and ideological questions, for example raised to this context: